j = 1 ∑ 2 n − 1 sin 2 ( 2 n + 1 π j ) 1 = B A C n − E D Find A + B + C + D + E
Bonus: Use this result to solve the Basel Problem
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Note that sin 2 N x = j = 0 ∑ N − 1 ( 2 j + 1 2 N ) ( − 1 ) j cos 2 N − 2 j − 1 x sin 2 j + 1 x = sin 2 N − 1 x cos x F N ( cot 2 x ) where F N ( X ) = j = 0 ∑ N − 1 ( − 1 ) j ( 2 j + 1 2 N ) X N − j − 1 = ( 1 2 N ) X N − 1 − ( 3 2 N ) X N − 2 + ⋯ It is clear that the roots of F N ( X ) are cot 2 2 N j π for 1 ≤ j ≤ N − 1 , and hence we deduce that j = 1 ∑ N − 1 cot 2 2 N j π = ( 1 2 N ) − 1 ( 3 2 N ) = 3 1 ( N − 1 ) ( 2 N − 1 ) and so j = 1 ∑ N − 1 c o s e c 2 2 N j π = N − 1 + 3 1 ( N − 1 ) ( 2 N − 1 ) = 3 2 ( N 2 − 1 ) Putting N = 2 n gives the sum 3 2 ( 4 n − 1 ) for this question, making the answer 2 + 3 + 4 + 2 + 3 = 1 4 .
We can prove the formula for ζ ( 2 ) without using the 2 n version of this result. Since sin x < x < tan x for 0 < x < 2 1 π , we obtain j = 1 ∑ n − 1 cot 2 2 n j π < π 2 4 n 2 j = 1 ∑ n − 1 j − 2 < j = 1 ∑ n − 1 c o s e c 2 2 n j π and hence 3 1 ( n − 1 ) ( 2 n − 1 ) < π 2 4 n 2 j = 1 ∑ n − 1 j − 2 < 3 2 ( n 2 − 1 ) which gives 1 2 n 2 ( n − 1 ) ( 2 n − 1 ) π 2 < j = 1 ∑ n − 1 j − 2 < 6 n 2 n 2 − 1 π 2 and the result is immediate, since the two outside terms both converge to 6 1 π 2 as n → ∞ .
How did you think of the first line? It seems quite amazing.
Problem Loading...
Note Loading...
Set Loading...
This sum is equal to 3 2 4 n − 3 2 . We can show this by induction. The base case of n=1 is straightforward. By the double angle identity for sin(x), 3 2 4 n − 3 2 = j = 1 ∑ 2 n − 1 sin 2 ( 2 n + 1 π j ) 1 = 4 1 j = 1 ∑ 2 n − 1 sin 2 ( 2 n + 2 π j ) cos 2 ( 2 n + 2 π j ) 1 We can use the identity 1 = cos 2 x + sin 2 x on the numerator inside the sum to get 4 1 j = 1 ∑ 2 n − 1 sin 2 ( 2 n + 2 π j ) 1 + cos 2 ( 2 n + 2 π j ) 1 = 4 1 j = 1 ∑ 2 n − 1 sin 2 ( 2 n + 2 π j ) 1 + 4 1 j = 1 ∑ 2 n − 1 sin 2 ( 2 n + 2 2 n + 1 π − π j ) 1 = 4 1 ( j = 1 ∑ 2 n + 1 − 1 ( sin 2 ( 2 n + 2 π j ) 1 ) − sin 2 ( 4 π ) 1 ) Rearranging where we started and where we ended up gives us j = 1 ∑ 2 n + 1 − 1 sin 2 ( 2 n + 2 π j ) 1 = 3 2 4 n + 1 − 3 2 which completes the proof.
Bonus: Because sin 2 ( x ) 1 = 1 + tan 2 ( x ) 1 , we have j = 1 ∑ 2 n − 1 tan 2 ( 2 n + 1 π j ) 1 = 3 2 4 n − 2 n + 3 1 Also, sin ( x ) ≤ x ≤ tan ( x ) ⟹ tan 2 ( x ) 1 ≤ x 2 1 ≤ sin 2 ( x ) 1 for 0 ≤ x ≤ 2 π so 3 2 4 n − 2 n + 3 1 ≤ j = 1 ∑ 2 n − 1 ( 2 n + 1 π j ) 2 1 ≤ 3 2 4 n − 3 2 ⟹ 3 2 − 2 n 1 + 3 ∗ 4 n 1 ≤ j = 1 ∑ 2 n − 1 4 π 2 j 2 1 ≤ 3 2 − 3 ∗ 4 n 2 Taking the limit as n goes to infinity gives 3 2 ≤ j = 1 ∑ ∞ 4 π 2 j 2 1 ≤ 3 2 ⟹ j = 1 ∑ ∞ j 2 1 = 6 π 2